Tennantite-(Hg), Cu6(Cu4Hg2)As4S13, a new tetrahedrite-group mineral from the Lengenbach quarry, Binn, Switzerland. (19th October 2021) - Biagioni, Cristian; Sejkora, Jiří; Raber, Thomas; Roth, Philippe; Moëlo, Yves; Dolníček, Zdenĕk; Pasero, Marco
Abstract: Tennantite-(Hg), Cu6 (Cu4 Hg2 )As4 S13, was approved as a new mineral species (IMA2020-063) from the Lengenbach quarry, Imfeld, Binn Valley, Canton Valais, Switzerland. It was identified as an aggregate of black metallic tetrahedral crystals, less than 0.1 mm in size, intimately associated with sinnerite, and grown on realgar. In reflected light, tennantite-(Hg) is isotropic, grey in colour, with creamy tints. Minimum and maximum reflectance data for COM wavelengths in air are [λ (nm): R (%)]: 470: 29.1; 546: 29.1; 589: 28.5; 650: 27.7. Electron microprobe analysis gave (in wt.% – average of 7 spot analyses): Cu 32.57(42), Ag 6.38(19), Tl 0.29(14), Zn 0.04(5), Hg 17.94(2.27), Pb 0.70(51), As 17.83(61), Sb 0.34(8), S 24.10(41), total 100.19(1.04). The empirical formula of the sample studied, recalculated on the basis of Σ Me = 16 atoms per formula unit, is (Cu4.69 Ag1.04 Tl0.03 )Σ5.76 (Cu4.35 Hg1.58 Pb0.06 Zn0.01 )Σ6.00 (As4.20 Sb0.05 )Σ4.25 S13.26 . Tennantite-(Hg) is cubic, I 4 3 m, with a = 10.455(7) Å, V = 1143(2) Å 3 and Z = 2. The crystal structure of tennantite-(Hg) has been refined by single-crystal X-ray diffraction data to a final R 1 = 0.0897 on the basis of 214 unique reflections with F o > 4σ( F o ) and 22 refined parameters. Tennantite-(Hg) is isotypic with other members of the tetrahedrite group. Mercury is hosted at the tetrahedrally coordinated M (1) site, in accord with the relatively long M (1)–S(1) distance (2.389 Å), similar to that observed in tetrahedrite-(Hg). Minor Ag is located at the triangularly-coordinated and split M (2) site. Other occurrences of tennantite-(Hg) are briefly reviewed and the Lengenbach finding is described within the framework of previous knowledge about the Hg mineralogy at this locality.